Evaluating palliative opportunities in pediatric patients with leukemia and lymphoma. (22nd March 2021) - Labudde, Emily J.; DeGroote, Nicholas P.; Smith, Susie; Ebelhar, Jonathan; Allen, Kristen E.; Castellino, Sharon M.; Wasilewski‐Masker, Karen; Brock, Katharine E.
Abstract: Background: Despite favorable prognoses, pediatric patients with hematologic malignancies experience significant challenges that may lead to diminished quality of life or family stress. They are less likely to receive subspecialty palliative care (PC) consultation and often undergo intensive end‐of‐life (EOL) care. We examined "palliative opportunities, " or events when the integration of PC would have the greatest impact, present during a patient's hematologic malignancy course and relevant associations. Methods: A single‐center retrospective review was conducted on patients aged 0–18 years with a hematologic malignancy who died between 1/1/12 and 11/30/17. Demographic, disease, and treatment data were collected. A priori, nine palliative opportunity categories were defined. Descriptive statistics were performed. Palliative opportunities were evaluated over temporal quartiles from diagnosis to death. Timing and rationale of pediatric PC consultation were evaluated. Results: Patients ( n  = 92) had a median of 5.0 (interquartile range [IQR] 6.0) palliative opportunities, incurring 522 total opportunities, increasing toward the EOL. Number and type of opportunities did not differ by demographics. PC consultation was most common in patients with lymphoid leukemia (50.9%, 28/55) and myeloid leukemia (48.5%, 16/33) versus lymphoma (0%, 0/4, p  = 0.14). Forty‐four of ninety‐two patients (47.8%) received PC consultation a median of 1.8 months (IQR 4.1) prior to death. Receipt of PC was associated with transplant status ( p  = 0.0018) and a higher number of prior palliative opportunities ( p  = 0.0005); 70.3% (367/522) of palliative opportunities occurred without PC. Conclusion: Patients with hematologic malignancies experience many opportunities warranting PC support. Identifying opportunities for ideal timing of PC involvement may benefit patients with hematologic cancers and their caregivers. Abstract : Palliative opportunities are events throughout a child's course with cancer that warrant additional palliative care support. Children with hematologic malignancies experienced a median of five palliative opportunities throughout their course, which increase toward death, yet received palliative care consultation only 47% of the time.